Social Change in Farming Community to The Development of West Java Internasional in Sukamulya Village - Marlianawati, Fitria; Setyowati, Dewi Liesnoor; Martitah, Martitah (Universitas Negeri Semarang, 2019)
The change in social interaction occur in the society especially agricultural community in Sukamulya due to the construction of West Java International Airport (BIJB). Social interaction is carried out by several people, among the community and the government to achieve the same goal, namely the creation of harmony and prosperity in society. The purpose of this study is to analyze social changes in development project West Java International Airport in Sukamulya. The research method used in this studywas qualitative. Informants in this study were 19 people consisting of 5 farmers, 3 traders, 3 airport employees, 5 village heads, and 5 community leaders, 2 village government officials, and 1 religious figure. Data collection techniques with observation were carried out by observing the daily behavior of the farming community on the impact of airport development, interviews were conducted with in-depth interviews with informants and documentation in this study includes photographs and documents that are considered important. The validity of the data in this study usedsource triangulation techniques. The results showed that interactions that occurred in society experience changes such as the weakening of mutual cooperation between communities, increasing individualistic attitudes, people's mindset becomes more productive, also more consumptive in lifestyle. Changes in livelihoods change people's mindset about the importance of education. Social inequalities that occurred in society were influenced by unequal income inequality of each community.